Environmental Enrichments for a Group of Captive Macaws: Low Interaction Does Not Mean Low Behavioral Changes - Reimer, Jessica; Maia, Caroline Marques; Santos, Eliana Ferraz (Routledge Journals, Taylor & Francis Ltd, 2016)
Environmental enrichment has been widely used to improve conditions for nonhuman animals in captivity. However, there is no consensus about the best way to evaluate the success of enrichments. This study evaluated whether the proportion of time spent interacting with enrichments indicated the proportion of overall behavioral changes. Six environmental enrichments were introduced in succession to 16 captive macaws, and interaction of the animals with them as well as the behaviors of the group were recorded before and during the enrichments. All of the enrichments affected the proportions of time spent in different behaviors. Macaws interacted more with certain items (hibiscus and food tree) than with others (a toy or swings and stairs), but introduction of the enrichments that invoked the least interaction caused as many behavioral changes as those that invoked the most. Moreover, feeding behavior was only affected by the enrichment that invoked the least interaction, a change not detected by a general analysis of enrichment effects. In conclusion, little interaction with enrichment does not mean little change in behavior, and the effects of enrichments are more complex than previously considered.
Keywords: Enrichment interaction; behavior; captivity; enrichment items